Olibanum Resin Coated Microcapsules of Gliclazide: Preparation and Evaluation for Controlled Release - Chowdary, K.P.R.; Panguluri, Srinivas; Enturi, Veeraiah (Asian Journal of Chemistry, 2010)
The objective of the study is to evaluate olibanum resin, a natural lipophilic polymer for its application as microencapsulating agent and to prepare and evaluate olibanum resin-coated microcapsules of gliclazide for controlled release. Controlled release formulations are needed for gliclazide for better control of blood glucose levels to prevent hypoglycemia, enhance clinical efficacy and patient compliance. Olibanum resin coated microcapsules of gliclazide were prepared by an industrially feasible emulsification-solvent evaporation method and the microcapsules were evaluated for controlled release. The resin coated microcapsules prepared are spherical, discrete, free flowing and multinucleate monolithic type. Microencapsulation efficiency was in the range 98-104 %. Gliclazide release from the microcapsules was slow over 24 h and depended on core:coat ratio, wall thickness and size of the microcapsules. Drug release from the microcapsules was by non-fickian diffusion mechanism. Good linear relationship was observed between wall thickness of the microcap-sules and release rate. Olibanum resin was found suitable as a new microencapsulating agent and the resin coated microcapsules exhibited good controlled release characteristics. Gliclazide release from the olibanum resin coated microcapsules, MC2 (size 20/30) was similar to that from Diamicron MR tablets, a commercial controlled release formulation of gliclazide.